Faktor-Faktor Yang Mempengaruhi Prestasi Usahawan Mikro Lepasan Program Inkubator Giatmara - Ishak, Ismadi (2019)
Micro enterprises represent the largest business entities that contribute to the Malaysian economy. In order to ensure the continuity of these micro businessses the government has proposed some programs to further develop the SME ventures which include business incubator development programs. This study was conducted to analyze the factors that contributes towards the success of GIATMARA's micro-entrepreneurship program through a special Incubator Development Program under the umbrella of GIATMARA that was conducted throughout Malaysia including Sabah and Sarawak. In addition, this study attempt to assess the survival of this GIATMARA's micro-entrepreneur program in the long-term by evaluating the performances of entrepreneurs, specifically by identifying the problems faced these entrepreneurs and by assessing the perception of these entrepreneurs based on the identifiable success factors. This study obtains feedback from 730 GIATMARA-born entrepreneurs in micro categories throughout Malaysia. A qualitative analysis was performed on the response received from the respondents. In achieving the predetermined objectives, several key analytical methods have been carried out, including Reliability Test, Correlation, and Regression analysis. The findings shows that there are three success factors that significantly contributes to the success of these micro-entrepreneurs. These are access to finance, marketing and business networking; all of which are important for the survival of the businesses. The findings also indicates that there were constraints that hinders the success of these entrepreneurs.